Differences in rates of percutaneous coronary intervention, cardiac surgery and all-cause mortality in indigenous and non-indigenous Australians with suspected acute coronary events. (25th November 2020) - Su, H.M.H; Kang, K; Seton, N.A; Gederts, S.R; Der, Y.S; Millhouse, J.D.S; Solayar, R.D; Perrin, E.L; Sartain, F.R; Ramkumar, S; Starmer, G.H
Abstract: Background: Indigenous populations globally are known to have lower revascularisation rates following acute coronary events and higher mortality partly due to inequitable access to specialised care like cardiac catheterisation. Whether these disparities persist when access is readily available is unclear. Purpose: We compared the rates of percutaneous coronary intervention (PCI), cardiac surgery, 30-day and long-term all-cause mortality in Indigenous (Aboriginal and Torres Strait Islanders) and non-Indigenous Australians in Far North Queensland (FNQ) – a region with a large Indigenous population and 24/7 cardiac catheterisation facilities. Method: All public patients in FNQ having their first inpatient angiogram from November 2012 to October 2019 were identified. The primary study outcomes were rates of PCI or cardiac surgery and all-cause mortality at 30 days and long term. Secondary study outcomes were significant left ventricular dysfunction (ejection fraction <50%) and valvular disease (moderate to severe) in the echocardiogram subset. Other differences in baseline characteristics, including age, gender, body mass index, postcode and indication for angiography were accounted for using logistic and cox regression analysis. Results: We identified 4489 patients (mean age, 61.7±13.0 years, 64.9% male, median follow-up 1045 days). 1042 (23.2%) self-identified as Indigenous. Indigenous patients were younger (53.7±11.6 vs 64.1±12.5 years, p<0.001), more likely female (45.5% vs 32.0%, p<0.001) and had small differences in angiography indications, ST elevation myocardial infarction (STEMI) 19.1% vs 18.1%, non-STEMI 45.7% vs 41.8%, angina 26.3% vs 28.0%, cardiac arrest 3.1% vs 3.7% and other 5.8% vs 8.4%, p=0.02. Rates of PCI or surgery 35.6% vs 38.5%, p=0.17, 30-day mortality 1.9% vs 2.7%, p=0.17 and long-term mortality 11.0% vs 11.5%, p=0.71 were similar in unadjusted data. 2959 patients (mean age, 62.1±13.0 years, 23.1% Indigenous, 64.9% male) were included in the echocardiogram subgroup. In unadjusted data Indigenous patients had similar rates of ventricular dysfunction 33.3% vs 31.3%, p=0.33 and valvular disease 19.4% vs 19.3%, p=0.93. After adjustment for other baseline characteristics, Indigenous patients had higher rates of PCI or cardiac surgery, OR 1.39 (95% CI, 1.18–1.64, p<0.001), ventricular dysfunction, OR 1.31 (95% CI, 1.07–1.60), p=0.01 and valvular disease, OR 1.93 (95% CI, 1.50–2.48), p<0.001. 30-day mortality was similar but Indigenous patients had higher adjusted long-term hazard of mortality, HR 1.80 (95% CI, 1.42–2.27), p<0.001. Conclusion: When cardiac catheterisation was readily available Indigenous patients had higher rates of PCI and cardiac surgery and similar 30-day mortality to non-Indigenous patients. Equitable access to healthcare improves outcomes but the nearly double long-term mortality of Indigenous patients shows more is required to help close the gap for disadvantaged populations. Funding Acknowledgement: Type of funding source: None